Acute Tocixity of Sterculia quadrifida R.Br Bark Ethanol Extract on Sprague-Dawley Rats - Siswadi Siswadi; Grace S. Saragih (Majalah Obat Tradisional, 2018)
Faloak (Sterculia quadrifida R.Br) is a medicinal plant used by people in the province of East Nusa Tenggara to treat hepatitis. This study aims to determine the acute toxicity of faloak (Sterculia quadrifida R. Br) bark ethanol extract in Sprague-Dawley (SD) male white rats. The method used is experimental using post-test only control group design. In this study the parameters used are body weight, clinical symptoms, clinical biochemistry (ALT & AST), histopathology of liver organ and mortality in rats. Twenty male Sprague-Dawley rats were randomly assigned to 5 groups, group 1 as control, group 2 was administered orally faloak bark ethanol extract at dose of 40 mg / kg body weight, group 3 at dose of 200 mg / kg body weight, group 4 at dose of 1000 mg / kg body weight and group 5 at dose of 5000 mg / kg body weight. Results of observation for 24 hours there are no dead rats, so the value of LD50 extract ethanol faloak is > 5,000 mg / kg body weight. Observations were conducted for 14 days to observed delayed occurrence of toxic effects. Oral administration of the faloak bark ethanol extract reduced the level of AST and ALT. The histopathology observation of rats liver cells showed liver cell necrosis at treatment doses of 200 - 5,000 mg / kg body weight.